Anticonvulsant Activity of Flower Extract from Telang Plant (Clitoria ternatea L) in Male Albino Mice Induced Strychnine - Erjon Erjon; Luluk Hasanah; Ensiwi Munarsih (LPPM Universitas Abdurrab, 2024)
The telang plant (Clitoria ternatea L.) has been reported to have sedative activity and has the potential as an anticonvulsant. The purpose of this study was to test the anticonvulsant activity of the flower extract of the telang plant on male albino mice of the Swiss Webster strain. The extraction process used the maceration method. Testing parameters included seizure onset, time of death and recovery time. The doses used were 100, 200, and 400 mg/kgbw, and diazepam was used as a comparison with a dose of 5 mg/kgbw. The results of this study indicate that the flower extract ot the telang plant at doses of 100, 200, and 400 mg/kgbw has anticonvulsant activity. Increasing the dose of the flower extract of the telang plant correlated very strongly with the prolongation of seizure onset. A dose of 400 mg/kgbw can prevent the death of mice in the convulsion model. The flower extract of the telang plant has the potential to be developed as an anticonvulsant.